TIPOLOGI KAWASAN JALAN PAGERAN ANTASARI BANJARMASIN - Nurfansyah Nurfansyah (Universitas Lambung Mangkurat, 2012)
Pangeran Antasariroadas one ofthe Banjarmasin City's maincorridor that have strategic functions for citydevelopment asthe center oftrade and services. The aim of this research was madein order to determinethe typologyandmorphologyof theexisting buildingonthe Pangeran Antasari Street of Banjarmasin. Expectedfromtheanalysis of thetypologyandmorphology ofthe building willobtaina typologyandmorphologyof the region.The methodof analysis usedin this research isthe evaluationand thecomparativemethod, thecomparison betweenthe theoryand the conditionsat the sites.In addition,this methodprovides an assessmentbased oncomparison ofthe variablesexamined inthe observations.Based on these resultsobtained by some element in typology and morphology that could make as building and massing in the sites, such as : SkyLine, Entrance, Landscape, SetBack, andhumanscale, therearequite relevantto thelocal regulationsis setforthePangeranAntasari Street of Banjarmasin, althoughexistingbuildingsstillless regularin terms ofmorphology.